(3GdMdd GdSfOSjI aj GdebGeGJ GdCMeOjI GdebOSjIs - (3SQGL GdOjf CHj GdYHGS CMeO Hf YHO GdMj GdMdHj GdefTC GdaGSj GdQMdIs; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3Hjbhd GdabjQ CMeO Hf YHOGdMj GdMdHj aEfg deG hdYJ HTQH eOGe GdUaG eY TQH eOGFM GdMHjH GdeUWai hcGf eef GSJhba fhGXQ GdfhGXQ GdebGeGJ GdMQjQjI s
(3BNQgG (B:s
(3hgPg GdebGeGJ CMb Cf JQaY Ydi GdQDS hJRa Ydi GdeMGad RaGa GdYQhS s
(3YGQV GdeDda HgG ebGeGJ GdMQjQjs
(3JHUQI GdYfhGf (B:s
(3eYGQVIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B418 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B264 s
Keywords: (3GdCOHs